Sobre Jorge Cañizares-Esguerra, How to Write the History of the New World: Histories, Epistemologies, and Identities in the Eighteenth-Century Atlantic World - Cheirif Wolosky, Alejandro (El Colegio de México, A.C., 2011)
-